2006
DOI: 10.1080/14769670500485513
|View full text |Cite
|
Sign up to set email alerts
|

Syllable structure, syllable duration and final lengthening in Parkinsonian French speech

Abstract: To cite this version:Danielle Duez. ABSTRACTThe present study investigates the duration of syllables with relation to position within phrases and the pattern of segment omissions within syllables in a text read by 12 French PD patients and 12 French control subjects. Three main tendencies emerged. The first was similar duration of syllables in PD and control speech, which may result from a combination of articulatory undershoot and slowness of speech gestures. The second was a normal incidence of segment omis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The abnormal speech rate has also been observed with diverging results during tasks used to elicit and evaluate continuous speech (usually reading tasks, as in the studies by Canter, 1963 ; Gräber et al, 2002 ; Martínez-Sánchez et al, 2016 ). Other studies, however, have found no intergroup differences between patients with PD and healthy individuals both in speech rate (Duez, 2006a , b ) and in articulation rate (Skodda and Schlegel, 2008 ).…”
Section: Introductionmentioning
confidence: 73%
“…The abnormal speech rate has also been observed with diverging results during tasks used to elicit and evaluate continuous speech (usually reading tasks, as in the studies by Canter, 1963 ; Gräber et al, 2002 ; Martínez-Sánchez et al, 2016 ). Other studies, however, have found no intergroup differences between patients with PD and healthy individuals both in speech rate (Duez, 2006a , b ) and in articulation rate (Skodda and Schlegel, 2008 ).…”
Section: Introductionmentioning
confidence: 73%
“…Several studies have reported a complex effect of PD on consonant and vowel duration. Despite the general agreement on shorter consonant durations in PD as compared to HC [ 27 29 ], vowel duration has been reported as shorter [ 29 ], longer [ 13 , 30 ] or similar [ 31 ] to healthy controls. Careful examination suggests that the inconsistency may come from heterogeneity of speech characteristics (particularly, speech rate of the PD group and segment type (e.g., articulation manner/place) and perhaps variation of speech severity across studies.…”
Section: Discussionmentioning
confidence: 99%
“…). Persons with PD produce words that are more variable in duration and shorter on average (Ackermann et al, ), although individual syllable duration may remain unchanged (Duez, ). Rats under the PD condition made shorter word calls on average, and this symptom was exacerbated by DBS (Fig.…”
Section: Discussionmentioning
confidence: 99%